Multiscale modeling and analysis for materials simulation - Du, Qiang; Weizhu, Bao (Lectures notes series / Institute for Mathematical Sciences, National University of Singapore, 2012)
The Institute for Mathematical Sciences at the National University of Singapore hosted a two-month research program on Mathematical Theory and Numerical Methods for Computational Materials Simulation and Design - from 1 July to 31 August 2009. This title collects four expanded lecture notes from the program along with self-contained tutorials